Relativity : A Very Short Introduction - Stannard, Russell (Oxford Oxford University Press, 2008)
Einstein's theory of relativity shattered the world of physics - replacing Newtonian ideas of space and time with bizarre and counter intuitive conclusions: a world of slowing clocks and stretched space, black holes and curved space-time. This Very Short Introduction explores and explains the theory in an accessible and understandable way.
Include Illustrations and Index.
A Very Short Introduction.
Keywords: Relativity -- Physics -- Physics - Relativity